Impacto produtivo de variáveis fisiológicas e climáticas e avaliação de ferramentas de diagnóstico nutricional de vacas em lactação em um rebanho comercial - Wlodarski, Leticia (2021)
The aim of this study was to evaluate the impact of physiological and climatic variables on milk production in a commercial herd in southern Brazil, to compare the visual method of estimating the body condition score (BCS) with ultrasound measurements of the backfat thickness (BFT) of cows and and compare pasture consumption values estimated by the ascending plate (PA) with those estimated by HerbValo. The study was carried out for eighteen months on a dairy farm in southern Brazil. Diets consisted of tropical or temperate pastures, supplemented with additional foodstuffs. A total of 137,997 records of milk production from morning and afternoon milkings were obtained, in addition to reproductive data from 210 cows. Additionally, air temperature and humidity data were obtained daily to calculate the Temperature and Humidity Index (THI). The milk production, climatic and qualitative data of the herd were submitted to cluster analysis and ordination analysis, through principal coordinate analysis. Paired ECC and EGS measurements were collected monthly over twelve months on 152 Holstein cows. Forage use was estimated monthly in up to four paddocks randomly selected (n = 40) by the PA and, in parallel, also by the HerbValo method. The values obtained by PA and HerbValo were compared using linear regression using PROC REG. Milk production was influenced by the month of the year, days of lactation and calving order. The THI and month of calving were inversely related to milk production. In general, both the BCS and the BFT were not affected by the month of the year. The linear relationship between BCS and BFT measurements was: EGS (mm) = 4.29ECC+ 5.17 (RMSE = 2.88; P<0.01; n = 669). Os valores de utilização da pastagem estimados pelo PA foram linearmente (P<0,01) relacionados aos estimados pelo HerbValo em tropical (declive = 1,01; R2 = 0,88) e temperadas (declive = 0,76; R2 = 0,54). The forage utilization estimated by PA and HerbValo for temperate pastures was on average 0.98 (±0.45) and 0.88 (±0.25) and, for tropical pastures, 0.89 (± 0.48) and 0.78 (± 0.26) ton MS/ha, respectively. The values of forage consumption estimated by the PA were also linearly related to those estimated by the HerbValo (P<0.01; R2 = 0.83) and were on average 7.2 (± 3.03) and 8.3 (± 2.45) kg DM/cow/day, respectively. Changes in the physical and nutritional characteristics of pastures offered throughout the year, as well as calving order and weather conditions, impact milk production. The change in the BFT of the cows was not detected precisely as a change in their BCS. Mean variability in body condition can be detected by EGS and ECC, so either tool is acceptable. Pasture utilization and consumption by a dairy herd in a subtropical pasture based system can be estimated by the HerbValo method.